Topically Used Herbal Products for the Treatment of Psoriasis – Mechanism of Action, Drug Delivery, Clinical Studies - Herman, Anna; Herman, Andrzej P. (Planta Medica, 2016)
Psoriasis is a chronic inflammatory skin disease characterized histologically by hyperproliferation and aberrant differentiation of epidermal keratinocytes. A wide range of conventional medical therapies to treat psoriasis is established, from topical therapies and systemic medications through to phototherapy or combinations of those. However, most of these therapies have a limited efficacy and may cause a number of side effects, including cutaneous atrophy, organ toxicity, carcinogenicity, and broadband immunosuppression, which are restricting their long-term use. Therefore, it would be desirable to use herbal products as an alternative treatment for psoriasis that causes fewer side effects. For this purpose, several electronic databases and literature references were used to summarize the current knowledge acquired on the basis of animal studies and clinical trials regarding herbal products used to treat psoriasis topically. This review discusses the mechanisms of herbal products activities through (1) inhibition of the keratinocyte hyperproliferation and inducing apoptosis, (2) inhibition of immune-inflammatory reaction, (3) suppression of phosphorylase kinase (PhK) activity, and (4) inhibition of the hedgehog (Hh) signaling pathway. Moreover, the penetration of herbal products through the psoriatic skin barrier, novel herbal drug delivery systems in psoriasis treatment, and possible adverse effects of herbal therapy are discussed.
Keywords: Psoriasis; herbal products; keratinocyte hyperproliferation; inflammatory reaction; skin barrier; herbal drug delivery systems